SMART MONEY MANAGEMENT IN THE DIGITAL ERA AT SMAN 16 BANDAR LAMPUNG - Mufahamah, Euis; Anita, Anita; Samosir, Amril; Pratama, Muhammad Irfan; Sejati, Hiro; Rahyono, Rahyono (MAJU : Indonesian Journal of Community Empowerment, 2025)
This study aims to educate and enhance digital financial literacy among students of SMAN 16 Bandar Lampung through the implementation of the smart money management concept, as well to provide an understanding of the growing dangers of online gambling among teenagers. In today’s digital era, easy access to financial technology, coupled with a lack of self-control, can lead to consumptive behavior and increase the risk of engaging in online gambling activities. The methods used in this activity include an educational approach through seminars, interactive discussions, and the dissemination of digital information media. The results show that students displayed high enthusiasm for wise financial management and an increased awareness of the social, legal, and psychological risks associated with online gambling. Early aducation on financial literacy and the dangers of online gambling has proven effective as a preventive measure in shaping students into financially intelligent and digitally ethical individuals..